PERLINDUNGAN HUKUM TERHADAP HAK CIPTA LAGU BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA (STUDI KASUS PUTUSAN MA NOMOR: 505 K/PDT.SUS-HKI/2021) - Rizana, Raden Herwin; Nasution, Abdul Razak (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
Copyright is the exclusive right of the creator that arises automatically based on the declarative principle after a work is realised in tangible form. Patents are exclusive rights granted by the state to inventors for their inventions in the field of technology for a certain period of time. The problem that will be discussed in this journal is how the Legal Protection of Song Copyrights based on Law Number 28 of 2014 concerning Copyright and how the author's analysis of decision number 505 K/Pdt.Sus-HKI/2021. The research method used is normative juridical, qualitative descriptive data analysis, The problem approach in this writing is a statutory approach (Statute Approach) and a case approach (Case Approach). The data used is secondary data. And the data collection method uses the document study method. Distribution of a toy doll product, Putri Anisa Hijab Perfumed Doll or Putri Anissa Hijab Perfumed Doll, which is sold freely by UD Go-Toys and PT Bintang Cahya Kencana, where one of the songs is the song "Aku Mau," created by Inge Christiane, the Central Jakarta Commercial Court granted a lawsuit from Inge Chritiane and ordered the defendants to pay material damages in a total amount of 4,000,000,000 - 4 billion rupiah. Supreme Court Decision Number 505 K/Pdt.Sus-HKI/2021, decided to reject the appeal from the defendants.The conclusion is that the legal protection of copyright aims to protect copyrighted works from duplication. Suggestions should be socialisation of the Copyright Act to the public is needed so that people know that every work there is the value of Intellectual Property.